停課不停學：當自主學習成為日常 #Learning Never Stops: When Self-Directed Learning Becomes Accustomed - 洪詠善 Yung-Shan Hung (Higher Education Foundation, 2020)
2020年初，一場新型冠狀病毒襲擊全世界，引發165個國家和地區實行學校停課，逾15億名學生受到影響。在「停課不停學」政策下，各國展開遠距學習資源與數位學習系統之研發及應用，提供不同對象與需求者能夠通過遠距自主學習提供心理支持及學習不間斷。本文在此脈絡下，論析面臨世界前所未見的大規模學校教育中斷的困境，當自主學習成為日常，學校如何轉化危機以因應新世紀最大規模的教學與學習方法的革新。本文從教育4.0趨勢造成的學習內容與經驗的改變，以新加坡為例分析自主學習的經驗；其次，從新課綱核心素養內涵與相關理論界定自主學習意涵；最後提出後設認知、導學、資訊科技應用、全校性自主學習模式，以及從 自我決定取向的四項設計要素，供相關政策規劃，以及學校與教師實踐之參考。 At the beginning of 2020, a severe special infectious pneumonia (COVID-19) attacked the world, causing 165 countries and regions to suspend school and affecting more than 1.5 billion students. Under the policy of "Leaning Never Stops," countries have launched the development and application of distant Education. To enrich learning resources and digital learning systems, governments provide learners with different needs and comfort psychological support and continuous learning. In the context, the paper aims to analyzes the dilemma faced by a large-scale school education interruption unprecedented in the world. When autonomous learning becomes accustomed, how does the school transform the crisis to cope with the largest innovation in teaching and learning methods in the 21 Century. First, it analyzes the experience of autonomous learning from the changes in learning content and experience caused by the trend of Education 4.0. Secondly, it defines the meaning of self-directed learning from the core competences connotation of the new Curriculum Guidelines and related theories. Finally, four models including metacognition, tutoring, information communication technology application, and school-wide self-directed learning, as well as four design elements from selfdetermination orientation are proposed for relevant policy enactment, as well as school and teacher practice reference.